A new species of Nephochaetopteryx Townsend (Diptera: Sarcophagidae) from the Brazilian Amazon mangrove forest - De-Souza, Caroline Costa; De Souza, Matheus Tavares; Da Silva Carvalho-Filho, Fernando (Zootaxa, 2022)
A new species of Nephochaetopteryx Townsend, Nephochaetopteryx aryi sp. nov., is described based on three male specimens from the Brazilian Amazon. They were collected with traps baited with rotting crustaceans (shrimp and crab) in a mangrove forest on the Atlantic coast, in the state of Pará.